Data Mining Usage and Applications in Health Services - Mehmet Akif Cifci; Sadiq Hussain (Politeknik Negeri Padang, 2018)
Data Mining (DM), used to extract large amounts of hidden, valuable, useful information in large quantities and to provide strategic decision support, has created a new perspective on the use of health data. It has become a rapidly growing method of responding to problematic areas of data in large quantities in almost all sections. Although in health services it seems to be slow, a major leap has come to the scene. The aim of this study is to provide a new perspective on decision-making processes by creating an infrastructure for the health data and to provide examples for healthcare workers in the healthcare industry using DM techniques. Forasmuch as, the conceptual framework of data discovery in databases, Data Warehousing, DM, Business Intelligence (BI) has been given. DM applications and usages are given as examples of priority issues and problem areas in the health sector.